Edukasi gema cermat penggunaan antibiotik dengan metode CBIA menggunakan Booklet di Desa Petaling Kabupaten Bangka - Sari, Lana; Zahriah, Zahriah; Lanaya, Dela; Purba, Ratih Puspita Kusumadewi (Universitas Mataram, 2025)
Based on BPS (2022) data, healthcare facilities in Mendo Barat District are very limited. There is only 1 polyclinic, 2 public health centers, and 2 pharmacies, making it difficult for some residents in remote areas to access available healthcare services. This situation encourages the community to engage in self-medication by purchasing antibiotics from general stores rather than seeking treatment at healthcare facilities. In Petaling Village, many people still use antibiotics freely and store them at home because they stop taking antibiotics when they feel better, which can increase cases of resistance. According to research by Sari & Purba (2024) on antibiotic usage knowledge using leaflet media, the difference between pretest and posttest scores in Petaling Village was not very significant, increasing from 54% to 66%. The partners for this activity are Petaling Village, Mendo Barat District, Bangka Regency. The activity was carried out on June 6th, 2024. The method used was a community empowerment education model to improve skills in selecting medications, known as the Active Learning Method (CBIA), utilizing booklets. The study results showed a significant difference in knowledge before and after providing antibiotic education using booklets, with a p-value of 0.001 > 0.05.